2006
DOI: 10.1080/00016480500395179
|View full text |Cite
|
Sign up to set email alerts
|

Protease-dependent activation of nasal polyp epithelial cells by airborne fungi leads to migration of eosinophils and neutrophils

Abstract: Fungi enhanced the production of chemical mediators from nasal epithelial cells. When nasal epithelial cells were activated with fungi, PAR2 and PAR3 mRNAs were more strongly expressed than in nonactivated cells. Eosinophil migration was induced by RANTES and eotaxin, and neutrophil migration was induced by IL-8 in HPECM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 17 publications
1
54
1
1
Order By: Relevance
“…Our findings are in keeping with previous studies that have reported the increase of pro-inflammatory cytokines, such as IL-8 [39], [59], [60] and chemokines, as GM-CSF [39], [61], [62], eotaxin [63], and MCP-1 [64] in CRSwNP, compared to control nasal mucosa. These cytokines and chemokines have been implicated in eosinophil inflammation in nasal polyps [1], [39], [62], [63] and are downregulated with glucocorticoid [39], [62], [65], [66] or anti-leukotriene [67] treatments.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in keeping with previous studies that have reported the increase of pro-inflammatory cytokines, such as IL-8 [39], [59], [60] and chemokines, as GM-CSF [39], [61], [62], eotaxin [63], and MCP-1 [64] in CRSwNP, compared to control nasal mucosa. These cytokines and chemokines have been implicated in eosinophil inflammation in nasal polyps [1], [39], [62], [63] and are downregulated with glucocorticoid [39], [62], [65], [66] or anti-leukotriene [67] treatments.…”
Section: Discussionsupporting
confidence: 93%
“…Fungal allergens also induce the production of chemokines, like IL-8, RANTES and eotaxin. These CC chemokines produced by nasal epithelial cells induce the migration of eosinophils [12]. Fungal allergens are diverse in their physiological, chemical and immunological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood eosinophils have been used in some co-culture studies with primary nasal epithelial cells, mainly to evaluate the effect of AEC-soluble factors on eosinophil migration and activation, but also how eosinophil soluble factors affect nasal epithelium [178,179,180]. Similar studies with AEC-conditioned medium have also been used to investigate mast cell proliferation and one group has investigated mast cell adhesion to tracheal epithelial cells in a canine system [181,182].…”
Section: The Accompanying Co-cultured Cellsmentioning
confidence: 99%